An Error Analysis of EFL Students’ Use of Simple Past Tense in Writing Narrative Text - Nahak, Yulia Ningsi; Sahan, Anselmus; Seran, Yanuarius (International Journal of English Education and Linguistics (IJoEEL), 2024)
This study investigated the errors in the use of the simple past tense in narrative texts written by tenth-grade students at SMA Negeri Taekas. Employing a descriptive quantitative approach, this research focused on identifying and analyzing errors using the surface strategy taxonomy. A total of 113 errors were identified and categorized into omission, addition, misformation, and misordering. The findings revealed that misformation were the most frequent errors (50%), followed by omission errors (32%). These results highlight the need for more targeted instruction in verb forms and tense usage, suggesting that more practice and explicit teaching of grammatical rules could significantly improve students’ writing accuracy.